Hydrogenation of Pyridines Using a Nitrogen‐Modified Titania‐Supported Cobalt Catalyst. Issue 44 (26th July 2018) - Chen, Feng; Li, Wu; Sahoo, Basudev; Kreyenschulte, Carsten; Agostini, Giovanni; Lund, Henrik; Junge, Kathrin; Beller, Matthias
Abstract: Novel heterogeneous catalysts were prepared by impregnation of titania with a solution of cobalt acetate/melamine and subsequent pyrolysis. The resulting materials show an unusual nitrogen‐modified titanium structure through partial implementation of nitrogen into the support. The optimal catalyst displayed good activity and selectivity for challenging pyridine hydrogenation under acid free conditions in water as solvent. Abstract : Nitrogen‐modified titanium structures : Cobalt catalysts were prepared by impregnation of titania with an aqueous solution of cobalt acetate and melamine. The resulting material has a distinctive nitrogen‐modified titanium structure and shows good activity and selectivity for pyridine hydrogenation in water.